'A threat to national unity, an emancipator': discourse construction of the Yoruba nation secessionist agitation in selected Nigerian digital communities. - Osisanwo, Ayo; Akano, Richard (Critical Discourse Studies, 2024)
The recently resurged Yoruba Nation (YN, henceforth) agitation joins some socio-political movements, social protests, and resistance group discourse in Nigeria that continue to gain traction in (critical) discourse studies. Guided by the theoretical paradigms of van Leeuwen's representational strategies and Martin and White's appraisal framework, 24 representative posts out of a thousand posts culled from Nairaland, Gistmania, and Naijaloaded generated between October 2020 and October 2021 were purposively selected and subjected to discourse analysis. Two levels of construction were realised: YN agitators and YN agitation. YN agitators were associated with four constructions: cowards, violence mongers, terrorists, and organised strategists. YN agitation was associated with three constructions: a threat to sovereignty and national unity, and emancipation from oppression. Negative labels manifested more than positives. The dominant negative constructs of the YN agitation manifested implicitly and explicitly through labelling, negative comparison, appeal to sentiments, expression of detest, and flaming, while the positive constructs manifested through encomium and appeal to ethnic benefit. Online participants do not only project and spread their ideological stances on the YN agitation; they also make efforts to suppress antithetical stances.